1966
DOI: 10.1080/00365521.1966.11800613
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Study of Ulcerative Colitis

Abstract: A group of 152 patients with a verified diagnosis of ulcerative colitis (including haemorrhagic proctitis) was compared with a control group with an identical sex ratio, age, and social class distribution. All patients attended an ulcerative colitis out-patient clinic, and had been examined and followed by the members of the team. By the use of questionnaires information was gathered concerning familial incidence of the following diseases: ulcerative colitis, regional ileitis, cancer of the colon and rectum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

1969
1969
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 1 publication
0
11
2
Order By: Relevance
“…There is evidence of a genetic predisposition to ulcerative colitis (Singer et al 1971, Binder et al 1966 and atopic disorders have been reported to be more common (Hammer et al 1968).There was only one atopic patient in the present study.…”
Section: Discussioncontrasting
confidence: 43%
“…There is evidence of a genetic predisposition to ulcerative colitis (Singer et al 1971, Binder et al 1966 and atopic disorders have been reported to be more common (Hammer et al 1968).There was only one atopic patient in the present study.…”
Section: Discussioncontrasting
confidence: 43%
“…Several studies [12][13][14] have shown possible onset of CD and UC in the same family, thus we have analyzed familial aggregation for the two diseases together. A multicentre study in Northern Italy [15] showed a positive family history (5.5%) comparable to the one observed in our study (7%).…”
Section: Discussionmentioning
confidence: 99%
“…Both diseases can occur in the same family [12][13][14]. Familial prevalence ranges between 1 and 23 percent according to selections of patients, diagnostic criteria and study design [12].…”
Section: Introductionmentioning
confidence: 99%
“…Familial and twins evidence indicates that predisposition to ulcerative colitis is determined by genetic factors (Wigley and MacLaurin, 1962;Almy and Plaut, 1965;Morris, 1965;Binder, Weeke, Olsen, Anthonisen, and Riis, 1966;Davidson, 1967). If the sex ratio for the early-onset group of ulcerative colitis is to be explained in genetic terms, then it seems that an X-linked factor has a dominant expression in some populations, to give a female preponderance, and a recessive expression in others, where male patients predominate.…”
Section: Genetic Aspectsmentioning
confidence: 99%
“…A polygenic scheme of this complexity can readily account for the positive associations between ulcerative colitis, and several other genetically based diseases, including Crohn's disease, sacroiliitis, ankylosing spondylitis, uveitis, chronic hepatic cirrhosis, eczema, and hay fever (Tumen, Monoghan, and Jobb, 1947;Pollard and Block, 1948;Comfort, Bargen, and Morlock, 1938;Willcox and Isselbacher, 1961;Holdsworth, Hall, Dawson, and Sherlock, 1965;Wright, Lumsden, Luntz, Sevel, and Truelove, 1965;Wright and Watkinson, 1965a, b;Binder et al, 1966;Billson, de Dombal, Watkinson, and Goligher, 1967;Korelitz and Coles, 1967;Hammer, Ashurst, and Naish, 1968). If one or more of the genes predisposing to ulcerative colitis also predisposes to these other diseases, then the positive associations between them can be explained.…”
Section: Genetic Aspectsmentioning
confidence: 99%